Designing and Implementing Physical Hypermedia Applications - Challiol, Cecilia (2006)
In this paper we present a design approach and a software framework for building physical hypermedia applications, i.e. those mobile (Web) applications in which physical and digital objects are related and explored using the hypermedia paradigm. We show how we extended the popular MVC metaphor by incorporating the concept of located object, and we describe a framework implementation using Jakarta Struts. We first review the state of the art of this kind of software systems, stressing the need of a systematic design and implementation approach; we briefly present a light extension to the OOHDM design approach, incorporating physical objects and “walkable” links. We next present a Web application framework for deploying physical hypermedia software and show an example of use. We compare our approach with others in this field and finally we discuss some further work we are pursuing.